Cardiac indexes, cardiac damage biomarkers and energy expenditure in professional cyclists during the Giro d'Italia 3-weeks stage race - Corsetti, R.; Lombardi, G.; Barassi, A.; Lanteri, P.; Colombini, A.; D'Eril, G. M.; Banfi, G. (Biochemia Medica, 2012)
The study of cardiac response to strenuous and continuous exercise is crucial to understanding the physiology of endurance. N-terminal proB-type natriuretic peptide (NT-proBNP) is a potential marker for monitoring myocardial wall stress, and troponins (TnT and TnI) are widely used in the diagnosis of cardiac ischemia and infarction. Strenuous exercise may generate transitory ischemia, myocardial stress, and diastolic left ventricular dysfunction, inducing the increased production of both these biomarkers. We measured changes in NT-proBNP and TnT in elite cyclists during a 3-week stage race, a model of strenuous exercise. MATERIALS AND METHODS: